2006
DOI: 10.1007/s00586-005-0045-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance image findings in the early post-operative period after anterior cervical discectomy

Abstract: If early neurological deterioration occurs following anterior cervical discectomy, the patient should be evaluated by urgent MRI scanning. In order to interpret such a scan it is essential to know what the normal post-operative MRI appearance is following an uncomplicated procedure. In the lumbar spine it is well recognized that early post-operative imaging following discectomy is difficult to interpret with a high rate of false positive scans. The normal appearance of MRI in the early post-operative period wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…Such technique of anterior decompression may also lead to increased residual posterior to uncovertebral junction after ACDF compared with posterior cervical keyhole foraminotomy. This finding was noticed by Bommireddy et al, 2 who reported that foraminal narrowing persisted in 66% of the first post-operative scans and did not resolve in the follow-up scans up to 6 months. Witzmann et al, 44 also emphasized the benefit of posterior cervical keyhole foraminotomy approach for removing disc fragment from lateral recess without the need for anterior cervical discectomy.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Such technique of anterior decompression may also lead to increased residual posterior to uncovertebral junction after ACDF compared with posterior cervical keyhole foraminotomy. This finding was noticed by Bommireddy et al, 2 who reported that foraminal narrowing persisted in 66% of the first post-operative scans and did not resolve in the follow-up scans up to 6 months. Witzmann et al, 44 also emphasized the benefit of posterior cervical keyhole foraminotomy approach for removing disc fragment from lateral recess without the need for anterior cervical discectomy.…”
Section: Discussionsupporting
confidence: 59%
“…22,27,29 The outcomes following Primary ACDF for cervical disc disease have been generally excellent, with high rates of clinical improvement and minimal rates of morbidity. 17,2,28,29,31,38 Unlike primary anterior cervical surgery, revision surgery may be difficult due to scarring. 23 Fused vertebrae may interfere with disc removal and requires aggressive bone removal, distorted soft tissue and bone anatomy may lead to an overall higher morbidity and lower cure rate.…”
mentioning
confidence: 99%
“…The Neck Disability Index (NDI) is the most widely-used neck-specific measure in published intervention studies (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). It has been cited in over 251 scientific articles and translated into more than 20 languages (available at http:// www.cmcc.ca/Portals/0/pdfs/rs_%20NDI_manual.pdf).…”
Section: Introductionmentioning
confidence: 99%
“…During 24-48 h after operation hematoma presents low intensity or moderate intensity on T 1 WI and moderate intensity or high intensity on T 2 WI. After acute stage, lesion presents hyper-intensity on both T 1 WI and T 2 WI, and heterogeneous intensity was also observed in few cases [4,9] .…”
Section: Spinal Stenosismentioning
confidence: 99%
“…Postoperative spinal infection presents a wide array of forms such as discitis, vertebral osteomyelitis and epidural abscess [4,[9][10][11] . Clinically, severe local pain is the principal manifestation of postoperative discitis and most cases can be cured by anti-inflammation treatment.…”
Section: Infectionmentioning
confidence: 99%